E-126 Current management of pulsatile tinnitus with venous causes. A large case series with mid- and long-term outcomes. (23rd July 2022) - Rustici, A; Cancelliere, N; Marotta, T; Spears, J; Mendes Pereira, V
Abstract : Introduction: Pulsatile Tinnitus (PT) is a disabling condition that can be caused by vascular anomalies. The treatment of the underlying vascular conditions may improve the PT, restoring the quality of life of many patients. Purpose: We aimed to investigate all vascular anomalies responsible for PT and their treatments, to assess the postoperative efficacy and the complication rate of endovascular treatments, as well as the influencing factors for recurrence. Materials and Methods: We reviewed all patients treated for PT in our institution between January 2020 and December 2021. We reviewed all clinical and imaging data, pre- and post-procedure, and patient outcomes to explore treatment efficacy and peri-operative morbimortality. Results: We included 114 patients in this study. All patients had undergone venous endovascular interventions for PT, 77% were women and 23% were men, with an average age of 52.0±15.0 years. Treatment strategies included: 53.8% venous sinus stenting (75% unilateral and 25% bilateral), 30.8% collateral venous occlusion by coiling (75% with the use of liquid embolic agent and 25% without additional agents), and 7.8% in combined stenting and coiling. The causes of PT included: intracranial stenosis in 63.3% (84.2% stenosis alone and 15.8% associated with prominent emissary veins), a high riding jugular bulb in 10% (33.3% isolated and 66.7% associated with diverticulum), prominent emissary veins in 13.3%, and an associated AVF in 13.3% of patients. No intraprocedural complications were reported. There were 2.3% of transitory peri-procedural complications. No permanent morbidity or mortality was observed. Conclusion: Endovascular treatment is a safe and effective treatment for venous causes of pulsatile tinnitus, achieving resolution of PT with low morbidity. Disclosures: A. Rustici: None. N. Cancelliere: None. T. Marotta: None. J. Spears: None. V. Mendes Pereira: None.